Financeirização e espaços sociais: as Zonas Especiais de Interesse Social (ZEIS) como mercado contestado - Pimenta, Ana Clara de Almeida (Universidade Federal de São Carlos, 2024)
The rapprochement between the financial sector and the built environment requires a constant metamorphosis of the strategies used to appropriate space. Characterized by the fixity and and because it is finite, land as a commodity imposes on capital the challenge of constantly exploring and expanding new frontiers so that it can explore and appropriate the potential income from the circumscribed perimeters of the metropolis. In contrast to this advance, the Special Zones of Social Interest (SZSI) have come as a disruptive force, constituting “urban borders” demarcated in an attempt to prevent speculative processes with the aim of transforming cities into more just, inclusive and democratic ones. Their demarcation brings with it collective struggles against historically legitimized inequalities led by segments of the population unable to access housing through the formal housing market. However, having been conceived as “non-market” spaces, prioritizing social well-being over purely market dynamics in their regulations, these areas have been transformed into new frontiers of expansion for capital, becoming a support for more sophisticated forms of market, financialization. Given this scenario, this thesis seeks to understand how areas of SZSI III and V, which appear as non-market spaces, become new frontiers for the installation of capital. In an effort to complete the aforementioned task, the study uses the theory of contested markets, developed by Ph.D. Philippe Steiner and Ph.D. Dr. Marie Trespeuch. Through this theory, the aim is to understand how these spaces have become a place of conflict where different agents seek to influence legal and regulatory structures in their favor.
Financialization and social spaces: Special Zones of Social Interest (ZEIS) as a contested market
Keywords: Financeirização; Mercados contestados; ZEIS; Região da Luz; Parceria público-privada; Revitalização; Financialization; Special zones of social interest; Contested markets; Luz region; Public-private partnership; Revitalization; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS